2023
DOI: 10.1007/s10644-023-09500-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of green finance and environmental protection on green economic recovery in South Asian economies: mediating role of FinTech

Abstract: Green finance and digital finance are cornerstones of sustainable growth. Given the significant investment and funding challenges that South Asia's new energy development faces, the potential role of digital finance in this situation is uncertain. Applying panel regression analysis and using a two-step generalized method of moments (GMM) to eliminate endogeneity, this study examines the connections between green finance, financial technology (FinTech), and high-quality economic development using data from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 72 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The green banking guidelines and Environmental and Social Risk Management (ESRM) policies, has been observed in several South Asian nations including Bangladesh, China, India, and Pakistan (Y. Q. Zhang, 2023), (Li, 2023). These nations have established comprehensive frameworks to encourage banks to adopt environmentally sustainable practices in their operations and investments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green banking guidelines and Environmental and Social Risk Management (ESRM) policies, has been observed in several South Asian nations including Bangladesh, China, India, and Pakistan (Y. Q. Zhang, 2023), (Li, 2023). These nations have established comprehensive frameworks to encourage banks to adopt environmentally sustainable practices in their operations and investments.…”
Section: Discussionmentioning
confidence: 99%
“…South Asian countries have made notable advancements in the implementation of green banking guidelines and policies to tackle environmental challenges and foster sustainable growth (Y. Q. Zhang, 2023). The significance of environmental and social risk management guidelines for the banking sector is steadily increasing.…”
Section: Discussionmentioning
confidence: 99%
“…A study of indicators for 66 countries conducted by Awais et al (2023) revealed that the acceleration of the Internet and the development of fintech have a positive effect on ecological economic activity and reduce carbon dioxide emissions. Studying green initiatives in three South Asian countries, Zhang (2023) found that fintech accelerates the issuance of green loans and promotes sustainable economic growth. Li et al (2023) determined that the development of financial technologies and digitisation as well as the quality of management of institutions reduces countries' dependence on natural resources.…”
Section: Financial Stability and Sustainable Growthmentioning
confidence: 99%
“…The current study concludes that green growth applications and strategies improved the country's financial stability in the short and long terms. However, Zhang (2023) digs deeper into the link between China's green growth, technical advancement, and the country's expanding financial sector. Long-term green growth in China is positively impacted by technology progress and both indicators of financial development.…”
Section: Literature Reviewmentioning
confidence: 99%